The context and nature of the evidence for metalworking from mid 4th millennium Yali (Nissyros) - Maxwell, V.; Ellam, R. M.; Skarpelis, N.; Sampson, A. (Journal of Greek Archaeology, 2019)
In the wider Aegean, it is now recognised that the very end of the Neolithic is a key period in the evolution of communities and in the roots of changes observed in the succeeding Early Bronze Age. One important aspect of this change was involvement in metallurgy. Establishing the nature of early metallurgy could enrich our understanding of the processes of change at work at this time.